New species of Carpophilus Stephens from Eastern Arunachal Pradesh, India (Coleoptera: Nitidulidae: Carpophilinae) - Dasgupta, Jhikmik (Zootaxa, 2024)
Carpophilus (Ecnomorphus) dhritibanerjeeae Dasgupta sp. nov. is described from Eastern Arunachal Pradesh in Northeastern India. The species is compared with the related species and illustrated. A key to the species of Carpophilus from Northeast India is appended.